How Safe is Eptifibatide during Urgent Carotid Artery Stenting? - Allam, Hesham; Vora, Nirav; Edgell, Randall; Callison, Richard C.; Al Khalili, Yasir; Storkan, Michelle; Alshekhlee, Amer (Frontiers in Neurology, 2013)
Background: Glycoprotein IIB/IIIA inhibitors are occasionally utilized during carotid artery stenting (CAS) in the presence or absence of a visualized intra-operative thrombus. Objective: We assess the hemorrhagic and clinical outcomes associated with the use of eptifibatide during CAS. Methods: A retrospective analysis of prospectively collected data on patients with the diagnosis of carotid artery stenosis underwent CAS in a single center. We identified those who received intravenous eptifibatide intra-operatively and compared to the rest of the cohort. Hemorrhagic outcomes included intracerebral hemorrhage (ICH) or groin hematoma that occurred during the hospital stay. Results: In this analysis, 81 patients had CAS during a 3-year span; 16 of those had received 15 mg of intravenous eptifibatide intra-operatively. The mean age of the treated and untreated patients was similar (65.6 ± 13.4 versus 65.4 ± 10.2; P = 0.13). One patient (1.2%) in this series had ICH in the perioperative period that occurred in the non-eptifibatide group. Five patients (6.2%) in this series had groin hematoma; only one in the non-eptifibatide group required surgical repair. No mortality was reported and clinical outcomes including discharge modified Rankin scale, NIH stroke scale, as well as discharge destination were similar in both groups. A stratified analysis among those who underwent an urgent CAS showed no significant differences in the risks of hemorrhages or any clinical outcome (P > 0.05). Conclusion: The use of eptifibatide during CAS is safe. The risk of any hemorrhagic complication is rare in this series; however, a prospective study to validate this observation will be helpful.